2016
DOI: 10.3109/10715762.2015.1133906
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of circulating oxidized LDL and HDL and fatty liver: the Cardiovascular Risk in Young Finns Study

Abstract: Oxidative reactions are thought to play a role in the inflammatory condition called fatty liver. It is unclear whether oxidized lipoprotein lipids or proteins are associated with future fatty liver. In the Cardiovascular Risk in Young Finns Study, we determined the circulating levels of LDL and HDL oxidized lipids and studied their associations with fatty liver assessed by ultrasonography. There were 1286 middle-aged subjects with normal liver and 288 subjects with fatty liver. Analysis of oxidized lipids cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Ours is the first study to report a favorable effect of a BFE formulation on oxLDL and oxLDL/HDL, which are considered more predictive of both cardiovascular and diabetic risk than traditional lipid or glycemic markers (Johnston et al 2006;Kaikkonen et al 2016;Mascarenhas-Melo et al 2013;Mitra et al 2011b). Decreases in both biomarkers trended to greater efficacy and statistical significance in the subgroup relative to all subjects, decreasing from −10% to −19% and from −17% to −25%, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Ours is the first study to report a favorable effect of a BFE formulation on oxLDL and oxLDL/HDL, which are considered more predictive of both cardiovascular and diabetic risk than traditional lipid or glycemic markers (Johnston et al 2006;Kaikkonen et al 2016;Mascarenhas-Melo et al 2013;Mitra et al 2011b). Decreases in both biomarkers trended to greater efficacy and statistical significance in the subgroup relative to all subjects, decreasing from −10% to −19% and from −17% to −25%, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Apart from ASCVD, circulating ox-LDL was also reported to be associated with diabetes, 40 , 41 metabolic syndrome, 42 obesity, 41 and fatty liver, 43 which may increase the risk of ASCVD.…”
Section: Association Between Circulating Ox-ldl and Atherosclerosismentioning
confidence: 99%
“…Nozomu Kono, et al . indicated that Lp-PLA 2 was protective against ox-LDL-induced hepatic injury, which is regarded as a leading cause of NAFLD 15 , 16 . In addition, Stanislav, et al .…”
Section: Discussionmentioning
confidence: 99%